TOWARDS THE DIGITAL MODERNISATION OF CIVIL REGISTRY OF UZBEKISTAN - Salimova Diyora Bakhtiyorjon kizi , (TADQIQOTLAR.UZ, 2023)
Annotation: In more recent years there have been numerous efforts to automate virtually every aspect of the civil registration process, and important applications of new technology have been introduced into the civil registration process of Uzbekistan. This article presents a brief overview of these developments.